afectaciones al derecho a un medio ambiente sano y a los derechos humanos ocasionados por la puesta en marcha de la central hidroeléctrica de itaipú (2019)
The incessant development of societies, seeking to satisfy each and every one of their needs, has led man to create different projects that without due planning have shaped the environment and have consequently involved several human rights, as they are the right to life, the right to health, the right to decent housing, among others. This was reflected in the development and operation of the Itaipú Hydroelectric Power Plant, which in order to make the hydroelectric use of the Paraná River’s hydraulic resources, caused environmental, physical, biotic, cultural, economic and political impacts that they significantly affected the environment and human rights. It is important to study this topic, since, in the contemporary world, it is recognized that the greatest degree of affectation to the environment originates from anthropogenic causes (Constitutional Court of Colombia, 2011, p.1). This affectation has caused the living conditions of living beings to decrease and, in the case of people, human rights have been violated and, consequently, human dignity has been violated.